Horse persulane management in cotton by allelopathic crop water extracts along with reduced doses of herbicides - Luqman, M; Musa, M; Iqbal, MS; Arshad, M; Rehman, HS (SAARC Journal of Agriculture, 2017)
The experiment was conducted at the field of University of Agriculture, Faisalabad, Pakistan to evaluate the performance of lower dose of herbicides in combination with allelopathic crop water leachates for controlling horse persulane (Trianthemaportulacastrum L.) weed in cotton field during two consecutive years of 2007 and 2008. Seven treatments viz., T1= control as weedy, T2= Pendimethalin @ 1.25 kg active ingredient (a.i.) ha-1(full dose) as pre-emergence, T3= Paraquat @ 200 g a.i. ha-1(full dose) direct shielded at 40 days after sowing (DAS), T4= Pendimethalin @ 0.417 kg a.i. ha-1(1/3 dose) as pre-emergence, T5= Paraquat @ 67g a.i. ha-1(1/3 dose) direct shielded at 40 DAS, T6=sorghum + sunflower + brassica + mulberry water extracts each @ 18 l ha-1 + Pendimethalin @ 0.417 kg a.i. ha-1(1/3 dose) as pre-emergence, and T7 = sorghum + sunflower + brassica + mulberry water extracts each @ 18 l ha-1 + Paraquat @ 67g a.i. ha-1(1/3 dose) direct shielded at 40 DAS were compared. Combination of water leachates of allelopathic crops with either 1/3 dose of Paraquat or with 1/3 dose of Pendimethalin were found more effective than other treatments for reducing density and dry weight of horse persulane at both the stages. Higher but identical number of bolls per plant, boll weight per plant and seed cotton yield were recorded in water leachates + 1/3 dose of Pendimethalin as pre-emergence, and water leachates + 1/3 dose of Paraquat direct shielded at 40 DAS. Higher gross return and gross margin were also obtained from the same treatments. The results revealed that sorghum, sunflower, brassica and mulberry water extracts each @ 18 l ha-1 in combination with 1/3 dose of Paraquat direct shielded at 40 DAS or with 1/3 dose of Pendimethalin as pre-emergence is economical, environment friendly and sustainable strategy for controlling horse persulane weed in cotton field in Pakistan. SAARC J. Agri., 15(1): 23-31 (2017)